2006
DOI: 10.1111/j.1365-2133.2006.07408.x
|View full text |Cite
|
Sign up to set email alerts
|

Substance P receptor expression in human skin keratinocytes and fibroblasts

Abstract: HaCaT cells and fibroblasts can express NK-1R at protein and transcription levels, and the expression was modulated by SP, IFN-gamma and Spantide I. This indicates that keratinocytes and fibroblasts are involved in the regulation of skin immunity and that NK-1R may play an important role in the pathogenesis of CAI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 31 publications
1
34
0
1
Order By: Relevance
“…Three new articles were retrieved this way, for a total of 13 articles concerning the action of CGRP and/or SP on cultured human skin fibroblasts, of which 12 were related to SP and 1 was related to both CGRP and SP. A summary of the content of these articles is shown in Table 1 [30,[50][51][52][53][54][55][56][57][58][59][60][61]. A schematic drawing is proposed showing the molecular mechanisms of CGRP and SP in human skin fibroblasts and is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three new articles were retrieved this way, for a total of 13 articles concerning the action of CGRP and/or SP on cultured human skin fibroblasts, of which 12 were related to SP and 1 was related to both CGRP and SP. A summary of the content of these articles is shown in Table 1 [30,[50][51][52][53][54][55][56][57][58][59][60][61]. A schematic drawing is proposed showing the molecular mechanisms of CGRP and SP in human skin fibroblasts and is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…SP can be a possible factor in the pathogenesis of cutaneous allergic inflammation. An investigation of the expression of NK-1R for SP in cultured human dermal fibroblasts and epidermal keratinocytes has reported that fibroblasts and keratinocytes can express NK-1R at both protein and transcriptional levels, and that this expression is upregulated by SP, gamma-interferon (IFN-gamma) and spantide I [55]. This suggests that fibroblasts and keratinocytes may be involved in the regulation of skin immune responses, and that NK-1R may play an important role in the pathogenesis of cutaneous allergic inflammation [55].…”
mentioning
confidence: 99%
“…3,27,28,31,54 Moreover, human keratinocytes and scalp HFs express NK1 receptors. 56 In culture, substance P stimulates proliferation of keratinocytes 57 and organ-cultured murine epidermis. 58 That substance P inhibited hair matrix keratinocyte proliferation in our assay, rather than stimulating it, underscores the very distinct, often underestimated, regulatory controls of HF versus epidermal keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, C-fiber plays pluripotential roles for itch-related events. For example, neuropeptides released from C-fibers stimulate keratinocytes and mast cells to produce pruritogenic factors that again stimulate C-fiber [3][4][5].…”
Section: Introductionmentioning
confidence: 99%